Visi Pendidikan Berbasis Agama, Filosofi, Psikologi dan Sosiologi - Sofyan Sauri; Faiz Karim Fatkhullah; Mugiarto Mugiarto (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2021)
The vision of education based on religion, philosophy, psychology and sociology is an educational effort in order to form intelligent human beings cognitively, behaviorally and also creatively in carrying out all kinds of activities. So that in today's modern era, strong human resources are needed in order to spread the vision and mission of education so that all problems that occur in society, the state and the nation will be able to be answered by prioritizing religious, philosophical, psychological and sociological approaches. This approach needs to be carried out as a human effort as khalifatullah fil ardi who is able to prosper this earth to provide benefits not only to humans but also to the universe that we live in as a manifestation of our gratitude to Allah